Carbon quantum dot as well as preparation method and application thereof
By using carbon quantum dots synthesized from tetracarboxyphenyl ethylene monomer as fluorescence probes, using their aggregation-induced fluorescence enhancement characteristics in the presence of Hg(II), portable, green, simple operation, high sensitivity and high selectivity Hg(II) detection is achieved, solving the problems of complex and expensive instruments and professional operations in the prior art, and achieving efficient and sensitive detection effects.
Patent Information
- Application Number
- CN202411627478.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to achieve portable, green, simple operation, high sensitivity and high selectivity Hg(II) detection, and common detection methods have complex sample preprocessing, expensive and poor portability instrument requirements, and professional operation requirements.
Carbon quantum dots synthesized from tetracarboxyphenyl ethylene monomers were used as fluorescence probes to prepare carbon quantum dots by solvothermal reaction, and their aggregation-induced fluorescence enhancement characteristics in the presence of Hg(II) were used for detection.
It realizes fast, efficient, sensitive and simple detection of Hg(II), with good specific selectivity and anti-interference, with a detection limit of 47nmol/L, meeting the needs of on-site detection.
Smart Images

Figure CN119614189A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterials and analytical testing technology, and in particular to a carbon quantum dot and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry, heavy metal pollution has become an important issue of environmental safety. Among metal ions, Hg(II) is considered to be one of the most dangerous metal pollutants, posing a major threat to human health and environmental ecology. When Hg(II) enters the human body, it will bind to the thiol groups in proteins, significantly affecting the mental and neurological functions of the human body, posing a huge threat to human health. Common methods for detecting heavy metal ions rely on inductively coupled plasma mass spectrometry (ICP-MS). However, this method usually involves complex sample pretreatment, long data acquisition time, expensive and poorly portable instruments, and requires professional operation, which is not conducive to rapid on-site detection outside the laboratory. Therefore, there is an urgent need for a portable, green, easy-to-operate, highly sensitive and highly selective Hg(II) detection technology.
[0003] Carbon quantum dots (CDs) are a type of carbon nanomaterial with significant fluorescence properties. They are quasi-spherical or spherical particles composed of carbon nanoparticles with a particle size of less than 10 nm. Carbon quantum dots have many advantages, such as excellent optical properties, good water solubility, low toxicity, and good biocompatibility. So far, there have been many different types of carbon quantum dots synthesized using various carbon sources. However, most of these carbon quantum dots are aggregation-induced quenching (ACQ) materials, which have the disadvantages of high fluorescence background, poor photostability, low fluorescence yield, and aggregation-induced self-quenching.
[0004] Aggregation-induced fluorescence enhancement (AIEE) materials are new materials with great research and application value proposed in recent years. The luminescence of this type of material is weak in the free state of a single molecule, but significantly enhanced in the aggregated state. The currently widely accepted AIE mechanism is that the restricted intramolecular motion (RIM) of molecules in the aggregated state leads to restricted non-radiative decay and high emission. At present, CDs with AIEE potential are still in the early stages of research and development, and the design and preparation methods of AIEE-type CDs and the mechanism of inducing AIEE still need to be further explored. Summary of the invention
[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a carbon quantum dot. The second purpose of the present invention is to provide a method for preparing the above-mentioned carbon quantum dot. The third purpose of the present invention is to provide the application of the above-mentioned carbon quantum dot or fluorescent probe in detecting Hg(II). The fourth purpose of the present invention is to provide a method for detecting Hg(II).
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A first aspect of the present invention provides a carbon quantum dot, wherein the carbon quantum dot is a carbon nanomaterial synthesized from tetra(4-carboxyphenyl)ethylene monomer.
[0008] Preferably, the particle size of the carbon quantum dots is about 2-6 nm.
[0009] Preferably, the maximum excitation wavelength of the carbon quantum dots in water is 400 nm.
[0010] Preferably, the maximum emission wavelength of the carbon quantum dots in water is 495 nm.
[0011] The second aspect of the present invention provides a method for preparing the carbon quantum dots described in the first aspect, comprising the following steps: mixing tetrakis(4-carboxyphenyl)ethylene with an organic solvent, and performing a solvothermal reaction to obtain the carbon quantum dots.
[0012] Preferably, the reaction temperature of the solvothermal reaction is 170-230°C.
[0013] More preferably, the reaction temperature of the solvothermal reaction is 190-210°C.
[0014] Preferably, the reaction time of the solvothermal reaction is 6-14 h.
[0015] More preferably, the reaction time of the solvothermal reaction is 8-12 h.
[0016] Preferably, the organic solvent is selected from one or more of N,N-dimethylformamide, tetrahydrofuran and acetonitrile.
[0017] Preferably, the usage ratio of tetrakis(4-carboxyphenyl)ethylene to the organic solvent is (1-10) mg:30 mL.
[0018] Preferably, the method further comprises the following steps: separating the reaction solution after the reaction to obtain a solid product, washing and drying to obtain the carbon quantum dots; the washing agent used for the washing comprises N,N-dimethylformamide.
[0019] More preferably, drying is carried out at 50-80°C.
[0020] The third aspect of the present invention provides the use of the carbon quantum dots described in the first aspect in detecting Hg(II).
[0021] The fourth aspect of the present invention provides a method for detecting Hg(II), comprising the following steps: mixing a test solution with the carbon quantum dots described in the first aspect to prepare a mixed solution, performing fluorescence spectrum detection on the mixed solution, and detecting that the test solution contains Hg(II) when an aggregation-induced fluorescence enhancement reaction occurs.
[0022] Preferably, the excitation wavelength used in the fluorescence spectrum detection is 380-420 nm.
[0023] Preferably, the emission wavelength used in the fluorescence spectrum detection is 495 nm.
[0024] Preferably, the mixed solution is incubated before fluorescence spectrum detection.
[0025] More preferably, the incubation time is 10-30 min.
[0026] More preferably, the incubation temperature is 0-60°C.
[0027] Preferably, the concentration of carbon quantum dots in the mixed solution is 0.01-1 mg / mL.
[0028] Preferably, the pH value of the solution to be tested is 3-7.
[0029] More preferably, the pH value of the solution to be tested is 4-6.
[0030] Preferably, the method comprises the following steps:
[0031] (1) mixing carbon quantum dots with a Hg(II) standard solution to obtain a mixed solution, detecting the fluorescence intensity of the mixed solution, and establishing a standard working curve;
[0032] (2) Mixing the test solution containing Hg(II) with the carbon quantum dots, detecting the fluorescence intensity thereof, and measuring the concentration of Hg(II) in the test solution according to the working curve constructed in step (1).
[0033] The beneficial effects of the present invention are:
[0034] The present invention provides a carbon quantum dot, which is a carbon nanomaterial synthesized from tetra(4-carboxyphenyl)ethylene monomers. The surface of the carbon quantum dot has abundant carboxyl groups, which can effectively capture mercury ions, and under the guidance of mercury ions, produce aggregation and significantly enhance the fluorescence intensity. In addition, the carbon quantum dots have good solubility in water, which is convenient for water phase detection. The carbon quantum dots belong to fluorescence enhancement probe materials, which only emit weak fluorescence by themselves, and the fluorescence is enhanced after acting with Hg(II). Compared with fluorescence quenching materials, the signal change of fluorescence enhancement is easier to detect effectively, and the background signal can be reduced, which is more suitable for application in biological systems.
[0035] The carbon quantum dots of the present invention are used to detect Hg (II) and produce specific fluorescence enhancement. The carbon quantum dots have good specific selectivity, anti-interference and high sensitivity for Hg (II) detection. A good linear relationship can be established between the fluorescence intensity of the solution and the Hg (II) concentration, and the detection limit is extremely low, which is 47 nmol / L. Therefore, the carbon quantum dots are used to detect Hg (II), which can achieve fast, efficient, sensitive and simple detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 TEM image of CDs prepared in Example 1;
[0037] Figure 2 is the infrared spectrum of CDs prepared in Example 1;
[0038] Figure 3 is the X-ray diffraction pattern of CDs prepared in Example 1;
[0039] Figure 4 is the UV-visible absorption spectrum of the CDs prepared in Example 1;
[0040] Figure 5 The fluorescence spectrum of the CDs prepared in Example 1 and the fluorescence spectrum of the aggregation-induced fluorescence phenomenon induced by Hg(II);
[0041] Figure 6 This is a linear relationship diagram of the CDs prepared in Example 1 used to detect Hg(II);
[0042] Figure 7 This is a diagram showing the selective experimental results of using the CDs prepared in Example 1 to detect Hg(II). DETAILED DESCRIPTION
[0043] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.
[0044] Drugs and reagents used in the following examples: Tetrakis(4-carboxyphenyl)ethylene was purchased from Aladdin Reagent, and the tetrakis(4-carboxyphenyl)ethylene was 1,1,2,2-tetrakis(4-carboxyphenyl)ethylene; N,N-dimethylformamide (DMF) was purchased from Myrel Reagent; all chemicals were at least analytical grade and no further purification was required before use; the experimental water was double distilled water.
[0045] Example 1
[0046] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0047] 50 mg of tetrakis(4-carboxyphenyl)ethylene was dissolved in 30 mL of DMF, and a mixed solution was obtained after ultrasonic dissolution; the mixed solution was transferred to a 50 mL polytetrafluoroethylene Teflon reactor, placed in an oven, and reacted at 200°C for 10 hours; after the reaction was completed, it was allowed to stand and cool to room temperature, and the reaction solution was centrifuged at 4000 rpm for 10 minutes to separate the supernatant to obtain a light yellow precipitate, which was repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate was placed in a vacuum drying oven at 60°C to dry to obtain carbon quantum dot powder, recorded as CDs, and the obtained carbon quantum dot powder was stored in a 4°C refrigerator.
[0048] Structural characterization of carbon quantum dots:
[0049] The transmission electron microscopy images of the CDs prepared in this example are as follows: Figure 1 As shown, the CDs are spherical with a particle size range of about 2-6 nm. Further magnification reveals an obvious lattice spacing of about 0.21 nm.
[0050] The CDs exhibit green light in deionized water and have low-intensity fluorescence characteristics.
[0051] According to the infrared spectrum of CDs ( Figure 2 ), proving the existence of functional groups on the surface of CDs, including OH in carboxylic acid groups at 3407 cm -1 The broad absorption peaks around and the stretching vibration of C=O (1705cm -1 ), stretching vibration of C–H inside the benzene ring (3034 cm -1 ) and the bending vibration of the benzene ring (1535cm -1 ), and the stretching vibration of C=C (1605cm -1 ).
[0052] To further study the structure of CDs, X-ray diffraction patterns were Figure 3 As shown, a significant broad diffraction peak signal was observed at about 25°, corresponding to the graphene sheets of the carbon core in small-sized (<10 nm) carbon quantum dots.
[0053] The UV-visible absorption spectra of CDs are shown in Figure 4 As shown, the strong absorption peaks at 250 nm and 296 nm are attributed to the π-π* transitions of the C=C bond and the aromatic ring, and the weak absorption peak at 332 nm is attributed to the n-π* transition of the C=O bond.
[0054] The fluorescence excitation and emission spectra of CDs are shown in Figure 2. Figure 5 As shown, its fluorescence maximum excitation wavelength is 400nm, and its maximum emission wavelength is 495nm.
[0055] Example 2
[0056] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0057] 10 mg of tetrakis(4-carboxyphenyl)ethylene was dissolved in 30 mL of DMF, and a mixed solution was obtained after ultrasonic dissolution; the mixed solution was transferred to a 50 mL polytetrafluoroethylene Teflon reactor, placed in an oven, and reacted at 200° C. for 10 hours; after the reaction was completed, it was allowed to stand and cool to room temperature, and the reaction solution was centrifuged at 4000 rpm for 10 minutes to separate the supernatant to obtain a light yellow precipitate, which was repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate was placed in a vacuum drying oven at 60° C. to dry to obtain carbon quantum dot powder, recorded as CDs, and the obtained carbon quantum dot powder was stored in a refrigerator at 4° C.
[0058] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0059] Example 3
[0060] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0061] 25 mg of tetrakis(4-carboxyphenyl)ethylene was dissolved in 30 mL of DMF, and a mixed solution was obtained after ultrasonic dissolution; the mixed solution was transferred to a 50 mL polytetrafluoroethylene Teflon reactor, placed in an oven, and reacted at 200°C for 10 hours; after the reaction, it was allowed to stand and cool to room temperature, and the reaction solution was centrifuged at 4000 rpm for 10 minutes to separate the supernatant to obtain a light yellow precipitate, which was repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate was placed in a vacuum drying oven at 60°C to dry to obtain carbon quantum dot powder, recorded as CDs, and the obtained carbon quantum dot powder was stored in a 4°C refrigerator.
[0062] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0063] Example 4
[0064] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0065] 100 mg of tetrakis(4-carboxyphenyl)ethylene was dissolved in 30 mL of DMF, and a mixed solution was obtained after ultrasonic dissolution; the mixed solution was transferred to a 50 mL polytetrafluoroethylene Teflon reactor, placed in an oven, and reacted at 200°C for 10 hours; after the reaction was completed, it was allowed to stand and cool to room temperature, and the reaction solution was centrifuged at 4000 rpm for 10 minutes to separate the supernatant to obtain a light yellow precipitate, which was repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate was placed in a vacuum drying oven and dried at 60°C to obtain carbon quantum dot powder, recorded as CDs, and the obtained CDs were stored in a 4°C refrigerator.
[0066] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0067] Example 5
[0068] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0069] 200 mg of tetrakis(4-carboxyphenyl)ethylene was dissolved in 30 mL of DMF, and a mixed solution was obtained after ultrasonic dissolution; the mixed solution was transferred to a 50 mL polytetrafluoroethylene Teflon reactor, placed in an oven, and reacted at 200°C for 10 hours; after the reaction was completed, it was allowed to stand and cool to room temperature, and the reaction solution was centrifuged at 4000 rpm for 10 minutes to separate the supernatant to obtain a light yellow precipitate, which was repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate was placed in a vacuum drying oven at 60°C to dry to obtain carbon quantum dot powder, recorded as CDs, and the obtained CDs powder was stored in a refrigerator at 4°C.
[0070] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0071] Example 6
[0072] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0073] Dissolve 50 mg of tetra(4-carboxyphenyl)ethylene in 30 mL of DMF, dissolve by ultrasonication, and obtain a mixed solution; transfer the mixed solution to a 50 mL polytetrafluoroethylene Teflon reactor, place it in an oven, and react at 170°C for 10 hours; after the reaction, cool it to room temperature, centrifuge the reaction solution at 4000 rpm for 10 minutes, separate the supernatant, obtain a light yellow precipitate, wash it repeatedly with DMF to remove unreacted impurities, and dry the purified precipitate in a vacuum drying oven at 60°C to obtain the aggregation-induced luminescence carbon quantum dot powder. The obtained carbon quantum dot powder is stored in a 4°C refrigerator.
[0074] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0075] Example 7
[0076] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0077] 50 mg of tetrakis(4-carboxyphenyl)ethylene was dissolved in 30 mL of DMF, and a mixed solution was obtained after ultrasonic dissolution; the mixed solution was transferred to a 50 mL polytetrafluoroethylene Teflon reactor, placed in an oven, and reacted at 230°C for 10 hours; after the reaction, it was allowed to stand and cool to room temperature, and the reaction solution was centrifuged at 4000 rpm for 10 minutes to separate the supernatant to obtain a light yellow precipitate, which was repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate was placed in a vacuum drying oven at 60°C to dry to obtain carbon quantum dot powder, recorded as CDs, and the obtained CDs powder was stored in a 4°C refrigerator.
[0078] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0079] Example 8
[0080] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0081] Dissolve 50 mg of tetrakis(4-carboxyphenyl)ethylene in 30 mL of DMF, and dissolve by ultrasonication to obtain a mixed solution; transfer the mixed solution to a 50 mL polytetrafluoroethylene Teflon reactor, place it in an oven, and react at 200°C for 6 hours; after the reaction, let it stand and cool to room temperature, centrifuge the reaction solution at 4000 rpm for 10 minutes, separate the supernatant, and obtain a light yellow precipitate, which is repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate is placed in a vacuum drying oven at 60°C to dry to obtain carbon quantum dot powder, recorded as CDs, and the obtained CDs powder is stored in a refrigerator at 4°C.
[0082] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0083] Example 9
[0084] This embodiment provides a carbon quantum dot, and the preparation method thereof is as follows:
[0085] Dissolve 50 mg of tetrakis(4-carboxyphenyl)ethylene in 30 mL of DMF, and dissolve by ultrasonication to obtain a mixed solution; transfer the mixed solution to a 50 mL polytetrafluoroethylene Teflon reactor, place it in an oven, and react at 200°C for 14 hours; after the reaction, let it stand and cool to room temperature, centrifuge the reaction solution at 4000 rpm for 10 minutes, separate the supernatant, and obtain a light yellow precipitate, which is repeatedly washed with DMF to remove unreacted impurities, and the purified precipitate is placed in a vacuum drying oven at 60°C to dry to obtain carbon quantum dot powder, recorded as CDs, and the obtained CDs powder is stored in a refrigerator at 4°C.
[0086] The structural characterization results of carbon quantum dots are similar to those of Example 1.
[0087] Experimental analysis
[0088] 1. Hg(II) detection limit test
[0089] Standard solution preparation: Prepare Hg(II) solutions of different concentrations. Add 100 μL of Hg(II) aqueous solutions of different concentrations into 800 μL of deionized water, mix well, and adjust the pH value to 5.0.
[0090] Detection solution preparation: Prepare CDs aqueous solutions of different concentrations, wherein the higher the CDs concentration, the stronger the fluorescence intensity of the fluorescent solution. The optional carbon quantum dot concentration is 0.25 mg / mL, 0.5 mg / mL, 0.75 mg / mL, 1 mg / mL, preferably 0.5 mg / mL.
[0091] The standard solution was mixed with 100 μL of 0.5 mg / mL test solution, and the test system was incubated for 20 min at 20°C. The effect of different concentrations of Hg(II) on the fluorescence signal of CDs was detected (the final concentration in the test system was 0.5,
[0092] 1, 2, 3 and 4 μmol / L). Under the excitation of 400 nm wavelength light, the fluorescence intensity of the light emitted by the CDs solution at 495 nm was detected and recorded as F, and the fluorescence intensity of the CDs itself was recorded as F0. The experiment was repeated 3 times and the results were averaged.
[0093] The response of CDs to different concentrations of Hg(II) was studied by fluorescence emission spectroscopy. Figure 6 As shown in Figure 2, the fluorescence intensity of CDs increases with the increase of Hg(II) concentration, and the linear relationship of the relative fluorescence intensity is F / F0=0.9359*[C Hg2+ ]+1.050, correlation coefficient R 2 =0.9918, and the linear range of Hg(II) detection is 0.5μmol / L~4μmol / L. The detection limit of the CDs is 47nmol / L, which meets the Hg(II) limit standard in the 2020 edition of the Pharmacopoeia of the People's Republic of China.
[0094] 2. Specific selective testing
[0095] In order to evaluate the specific selectivity of the above CDs for Hg(II) and other interfering ions, various ions (Au 3+ , Cu 2+ 、Cd 2+ , K + , Ca 2+Mg 2+ , Mn 2+ 、Ni 2+ 、Co 2+ , Ba 2+ , Cl - 、F - ) at a concentration of 5 μmol / L on the fluorescence intensity of CDs. Figure 7 As shown in the figure, CDs only showed an obvious aggregation-induced fluorescence enhancement reaction to Hg(II), and other ions had no significant effect on the probe fluorescence intensity. The above results show that the CDs has good selectivity and aggregation-induced fluorescence enhancement (AIEE) characteristics, and can be used to detect Hg(II).
[0096] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A carbon quantum dot, characterized in that The carbon quantum dots are carbon nanomaterials synthesized from tetra(4-carboxyphenyl)ethylene monomers.
2. The carbon quantum dots according to claim 1, characterized in that The particle size of the carbon quantum dots is about 2-6 nm.
3. The method for preparing carbon quantum dots according to claim 1 or 2, characterized in that: The method comprises the following steps: mixing tetra(4-carboxyphenyl)ethylene with an organic solvent, and performing a solvent thermal reaction to obtain the carbon quantum dots.
4. The method for preparing carbon quantum dots according to claim 3, characterized in that: The reaction temperature of the solvent thermal reaction is 170-230°C; And / or, the reaction time of the solvent thermal reaction is 6-14h.
5. The method for preparing carbon quantum dots according to claim 3, characterized in that: The method further comprises the following steps: separating the reaction solution after the reaction to obtain a solid product, washing and drying to obtain the carbon quantum dots; the washing agent used in the washing comprises N,N-dimethylformamide.
6. Use of the carbon quantum dots according to claim 1 or 2 in detecting Hg(II).
7. A method for detecting Hg(II), characterized in that: The method comprises the following steps: mixing a test solution with the carbon quantum dots according to claim 1 or 2 to prepare a mixed solution, performing fluorescence spectrum detection on the mixed solution, and detecting that the test solution contains Hg(II) when an aggregation-induced fluorescence enhancement reaction occurs.
8. The method for detecting Hg(II) according to claim 7, characterized in that The excitation wavelength used in the fluorescence spectrum detection is 380-420 nm.
9. The method for detecting Hg(II) according to claim 7, characterized in that The concentration of carbon quantum dots in the mixed solution is 0.01-1 mg / mL.
10. The method for detecting Hg(II) according to claim 7 or 8, characterized in that The steps include: (1) mixing carbon quantum dots with a Hg(II) standard solution to obtain a mixed solution, detecting the fluorescence intensity of the mixed solution, and establishing a standard working curve; (2) Mixing the test solution containing Hg(II) with the carbon quantum dots, detecting the fluorescence intensity thereof, and measuring the concentration of Hg(II) in the test solution according to the working curve constructed in step (1).